THE IMPACT OF MONETARY POLICY SHOCKS IN INDONESIA - Phany Ineke Putri (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
Monetary policy is an important policy of a country in maintaining balance in the economy. This study aims to test impact of monetary policy shocks in Indonesia against to economic variables. The data used in this study are the level of domestic prices (P), economic growth (EG), interest rates (IR), and the real exchange rate (R) with quarterly time periods in 2019-quarter 3 in 2021. This research used the Structural Vector model Autoregression (SVAR). The result shows that the contribution of monetary policy instruments varies considerably to economic variables such as economic growth, the level of domestic prices, and the real exchange rate. But, the biggest contribution of the BI rate is felt by the variable price (inflation).